2014
DOI: 10.1371/journal.pone.0112635
|View full text |Cite
|
Sign up to set email alerts
|

Lipo-Chitin Oligosaccharides, Plant Symbiosis Signalling Molecules That Modulate Mammalian Angiogenesis In Vitro

Abstract: Lipochitin oligosaccharides (LCOs) are signaling molecules required by ecologically and agronomically important bacteria and fungi to establish symbioses with diverse land plants. In plants, oligo-chitins and LCOs can differentially interact with different lysin motif (LysM) receptors and affect innate immunity responses or symbiosis-related pathways. In animals, oligo-chitins also induce innate immunity and other physiological responses but LCO recognition has not been demonstrated. Here LCO and LCO-like comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…The intracellular receptors NOD1 and NOD2 have been shown to bind the peptidoglycan fragments Tri-DAP and muramyl-dipeptide, respectively (7), but it is unknown if the mammalian immune system is capable of recognizing the ubiquitous polymeric glycan backbone of peptidoglycan. Furthermore, a recent study suggested that chitin oligomers may modulate mammalian angiogenesis through interactions with a yet unknown receptor (8). We hypothesized that the LysMD family may represent a novel family of pattern recognition receptors, potentially capable of recognizing important microbial ligands such as peptidoglycan or chitin.…”
Section: Introductionmentioning
confidence: 99%
“…The intracellular receptors NOD1 and NOD2 have been shown to bind the peptidoglycan fragments Tri-DAP and muramyl-dipeptide, respectively (7), but it is unknown if the mammalian immune system is capable of recognizing the ubiquitous polymeric glycan backbone of peptidoglycan. Furthermore, a recent study suggested that chitin oligomers may modulate mammalian angiogenesis through interactions with a yet unknown receptor (8). We hypothesized that the LysMD family may represent a novel family of pattern recognition receptors, potentially capable of recognizing important microbial ligands such as peptidoglycan or chitin.…”
Section: Introductionmentioning
confidence: 99%
“…An activity-guided rat aorta ring bioassay with a proven ability to identify anti-angiogenic compounds [ 33 ] was modified by reducing the concentration of HIFCS from 20% to 5% [ 36 ]. This slowed the rate of tube formation but enabled the screening of pro- and anti-angiogenic activities over three consecutive days.…”
Section: Discussionmentioning
confidence: 99%
“…The rat aorta angiogenesis bioassay [ 33 ] was modified to enhance the ability to screen for pro-angiogenic activity in the HPLC-derived fractions by reducing the concentration of heat inactivated foetal calf serum (HIFCS) from 20% to 5% and incubating for 7 days in 48 well culture plates (Costar, Corning, Lowell, MA) at 37°C in 5% CO 2 [ 36 ]. Six technical and three biological replicates were used and the medium was changed on day 4 of culture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, such a mechanism has been shown to operate in the legume Lotus japonicus , in which a LysM domain-containing kinase that mediates the response to pathogens exhibits much higher sensitivity to chitin as compared to Nod factors [ 19 ]. In mammalian cells, the ability of Nod factors (lipochitin oligosaccharides) to stimulate mammalian angiogenesis [ 20 ], taken with the previously mentioned observation that a Nod factor is able to suppress a plant innate immune reaction in species that lack the Nod receptor [ 14 ], suggests that physiologically relevant cross-activation is possible. For example, a chitin derived molecule could bind a LysM domain that normally binds Nod factor ( Fig 2 , left).…”
Section: Introductionmentioning
confidence: 99%